Respostas
respondido por:
1
a)
(x - 5) (x - 6) = 30
x² - 6x - 5x + 30 = 30
x² - 11x = 30 - 30
x² - 11x = 0
x (x - 11) = 0
x' = 0 x'' = 11
b)
9x² = 25 + 8x²
9x² - 8x² = 25
x² = 25
x' = √25 x'' = - √25
x' = 5 x'' = - 5
c)
64x² - 1 = 0
64x² = 1
x² = 1/64
x' = √(1/64) x'' = - √(1/64)
x' = 1/8 x'' = - 1/8
(x - 5) (x - 6) = 30
x² - 6x - 5x + 30 = 30
x² - 11x = 30 - 30
x² - 11x = 0
x (x - 11) = 0
x' = 0 x'' = 11
b)
9x² = 25 + 8x²
9x² - 8x² = 25
x² = 25
x' = √25 x'' = - √25
x' = 5 x'' = - 5
c)
64x² - 1 = 0
64x² = 1
x² = 1/64
x' = √(1/64) x'' = - √(1/64)
x' = 1/8 x'' = - 1/8
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás